Gender Differences in Effective Participation of the Elected People’s Representatives to the Union Parishads of Bangladesh: Token Presence or Effective Participation - Talukdar, Imdadul Haque; Karin Österman; Kaj Björkqvist (European Journal of Social Science Education and Research, 2021)
Effective political participation was measured with a questionnaire that was completed by 680 (347 female, 333 male) representatives to the rural local governance of Bangladesh, Union Parishads. The questionnaire included four scales. Females scored significantly lower than males on the scales of having influence on political decisions, active political participation and initiatives, and political commissions of trust; and significantly higher on victimisation from faulty meeting procedures. Influence on political decisions varied according to age group for females but not for males. Of the males, 94.7 percent participated in meetings regularly compared to only 30.1 percent of the females. Of the females, 16.9 percent reported they were not informed about the time of the meetings, while this was the case for only 3.7 percent of the males. None of the committees used voting at the monthly meetings. Of the males, 94.9 percent reported that meeting decisions were taken through mutual understanding, while only 15.3 percent of the females were of that opinion. Of the females, 64.8 percent reported that decisions were taken by the chairman alone, and 19.9 percent of them that decisions were taken by the chairman and male members only. It may be concluded that despite recent legislative measures, female political participation still needs to be improved in Bangladesh.